Estimate for the Arithmetical Cost of an Algebraic Multigrid Preconditioner - Ranjbar, Amir (Mathematical Problems of Computer Science, 2021)
A multigrid preconditioner for the matrix arising in finite element approximation of model elliptic boundary value problem is proposed. Hierarchical triangular grids with bisection form the basis of multigrid construction. The main purpose of the paper is to evaluate the arithmetical cost of a preconditioner step.